Occupation and risk of knee osteoarthritis and knee replacement: a longitudinal, multiple-cohort study - Perry, TA; Wang, X; Gates, L; Parsons, CM; Sanchez-Santos, MT; Garriga, C; Cooper, C; Nevitt, MC; Hunter, DJ; Arden, NK (Elsevier, 2020)
Objectives : To examine the effect of occupation on knee osteoarthritis (OA) and total knee replacement (TKR) in working-aged adults.